STRATEGY TO INCREASE SATISFACTION IN SHAPING STUDENT BEHAIOR IN STIKES HARAPAN BANGSA PURWOKERTO - Yuliarti, Lusi (STIE AUB Surakarta)
The purpose of this research is to know the influence of physical evidence, location,and image on satisfaction on the loyality of college student in the STIKES Harapan Bangsa Purwokerto. This study is a survey. The data is primary data taken by sampling method, as many as 125 respondents. Data analyzed with validity and reliability test, partial test ( t test ), simultaneously test ( F test ), R-square and path analysis. T test result shows that : physical evidenc is significant positive effect on satisfaction, location is insignificant positive effect on satisfaction, image is insignificant positive effect on satisfaction, physical evidenc is significant positive effect on loyality, location is insignificant positive effect on loyality, image is insignificant negatie effect on loyality, satisfaction is significant positive effect on loyality. F test result shows that simultaneously physical evidence, location,and image has significant positive effect on the performance. R-square test result shows that 84,7 % variation of loyality can be explained by physical evidence, location, image,and satisfaction the remaining 15,3% is explained by other factors out of the model. The path analysis show : the direct effect of physical evidence on loyality variables is smaller than the indirect effect of physical evidence on loyality by mediating satisfaction. Based on a total leverage to improve loyality will be more effective if through increased discipline by mediating satisfaction Keywords : physical evidence, location, image, satisfaction, loyality